Penerapan Metode Takrir Dalam Meningkatkan Capaian Hafalan Santri Rumah Tahfidz Al-Kifach - Virza Maulana Abdillah; Bahar Agus Setiawan; Siti Nursyamsiyah (Yayasan Madinah Al-Aziziyah, 2026)
The importance of maintaining the quality of Quranic memorization amidst the naturally elusive nature of memory. The primary challenge frequently faced by students (santri) at Rumah Tahfidz Al Kifach is the difficulty in balancing the addition of new memorization (ziyadah) with the retention of previously memorized verses (muraja’ah). This study aimed to analyze the effectiveness of implementing the takrir (repetition) method as a solution to enhance students' memorization achievements. This study employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The results indicated that the implementation of the takrir method was highly effective in improving students' memorization outcomes. Through consistent repetition, students were able to transfer their memorization from short-term memory to long-term memory, rendering the memorization more fluent (mutqin) and less prone to forgetfulness. Furthermore, this method was proven to help students develop tongue reflexes and memory sharpness, thereby making the process of adding new memorization faster and more stable. This study concludes that the takrir method serves as the primary foundation in the learning system at Rumah Tahfidz Al Kifach, where discipline in repetition is directly proportional to the quality and quantity of memorization achieved by the students.